International Oil and Gas Conference and Exhibition in China 2010
DOI: 10.2118/130726-ms
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments and Updated Screening Criteria of Enhanced Oil Recovery Techniques

Abstract: This paper reviews recent developments in enhanced oil recovery (EOR) techniques published in SPE conference proceedings for 2007 to 2009. It also updates the EOR criteria developed by Taber et al. in 1996 based on field applications reported in Oil & Gas Journal and at various SPE conferences. It classifies EOR methods into five main categories: gas-based, water-based, thermal, others, and combination technologies. New developments in EOR techniques, chemicals, and mechanisms are summarized to clarify adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(20 citation statements)
references
References 98 publications
1
19
0
Order By: Relevance
“…Enhanced oil recovery (EOR) screening, carried out based on Al-Adasani and Bai [1], revealed that the Tempino and Kenali Asam reservoirs are very suitable for polymer flooding; they were ranked in first place. Austad, et al [2], followed by Samanta [3], have reported that significant improvements can be obtained by co-injecting surfactant and polymer at a rather low chemical concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced oil recovery (EOR) screening, carried out based on Al-Adasani and Bai [1], revealed that the Tempino and Kenali Asam reservoirs are very suitable for polymer flooding; they were ranked in first place. Austad, et al [2], followed by Samanta [3], have reported that significant improvements can be obtained by co-injecting surfactant and polymer at a rather low chemical concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Flue gases injection results in increased volume of being a consequence of CO 2 dissolving and considerably lower viscosity. 2 [11], therefore the criteria assumed when selecting the most appropriate N 2 deliveries should be made. The equipment needed for gas capturing, cleaning and compress-…”
Section: Flue Gases Injection Methodsmentioning
confidence: 99%
“…The ranges and average values of parameters characterizing oil and reservoir are indicated. It must be born in mind that the presented values are only of informative character and should not be treated as constant threshold values [2].…”
Section: Introductionmentioning
confidence: 99%
“…He also offered technical screening guides for EOR nowadays known as Taber's tables (Taber et al, 1997a,b). Different authors (Parkinson et al, 1991;Cheng, 2001;Morooka et al, 2001;de Cristo, 2003;Wang, 2003;Korb and Nicholson, 2004;Mohaghegh, 2005;Aladasani and Bai, 2010;Fahad et al, 2011;Zerafat et al, 2011;Ivanov and Roslyak, 2012) have given comparison of various methods and screening criteria, relying on engineering constraints, economic and environmental aspects. In particular, Siena et al 's (2015) study, based on the analogues rheological properties of collectors in different geographical areas eastern and western hemispheres, EOR methods were ranked using a hierarchical Bayesian classification by deterministic input information.…”
Section: Introductionmentioning
confidence: 99%